2015
DOI: 10.1021/bi500957g
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical Comparison of Soluble Amyloid-β(1–42) Protofibrils, Oligomers, and Protofilaments

Abstract: Some of the pathological hallmarks of the Alzheimer's disease brain are senile plaques composed of insoluble amyloid-β protein (Aβ) fibrils. However, much of the recent emphasis in research has been on soluble Aβ aggregates in response to a growing body of evidence that shows that these species may be more neurotoxic than fibrils. Within this subset of soluble aggregated Aβ are protofibrils and oligomers. Although each species has been widely investigated separately, few studies have directly compared and cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 48 publications
0
39
0
Order By: Relevance
“…It may also increase the likelihood of A␤ fibrils to fragment to compensate for the increased side chain flexibility, explaining the truncated fibril structures observed by TEM (61,62). These two modes of disruption would be relatively independent of the main chain interactions and result in the maintenance of the conventional ␤-strand structure, resulting in an aggregate species that resembles a protofibrillar structure (63,64).…”
Section: Resultsmentioning
confidence: 99%
“…It may also increase the likelihood of A␤ fibrils to fragment to compensate for the increased side chain flexibility, explaining the truncated fibril structures observed by TEM (61,62). These two modes of disruption would be relatively independent of the main chain interactions and result in the maintenance of the conventional ␤-strand structure, resulting in an aggregate species that resembles a protofibrillar structure (63,64).…”
Section: Resultsmentioning
confidence: 99%
“…We have previously detailed the preparation and characterization of the biophysical and proinflammatory properties of protofibrils rapidly formed by Aβ42 and to a slower extent by Aβ40 [44, 45, 49]. A variety of solution and microscopic techniques indicated that Aβ42 protofibrils were short, curvilinear species less than 100 nm in length, rich in β-sheet structure, yet relatively small and quite soluble (hydrodynamic radius, R H 20–25 nm and molecular weight, M w , 200–2600 kDa).…”
Section: Resultsmentioning
confidence: 99%
“…A solution of Aβ42 alone yielded a typical 2-peak elution profile on Superdex 75 (fractionation range 3–70 kD) with roughly equivalent amounts of protofibrils and monomers (Figure 1A). Our previous work showed that protofibrils were larger than 70 kD [49], so protofibrils eluted in the void volume. The calculated distribution was 56% protofibrils and 44% monomers (Figure 1B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…35 We used HFIP/NaOH treatment for the preparation monomeric Aβ peptide. Briefly, lyophilized Aβ(1-42) peptide was dissolved in HFIP and stored at -80 °C.…”
Section: Preparation Of Aβ(1-42) Monomer Stock Solutionmentioning
confidence: 99%